Writing and revision : the effect of individual revision, peer revision and teacher's written feedback in foreign language text production - Dellagnelo, Adriana de Carvalho Kuerten (1997)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão